The legal nature of the sermon in Algerian law - Yahia, Abdelaziz (Journal of Human Sciences, 2022)
This research deals with the concept of engagement, its legitimacy from the Book and the Sunnah, and its importance as a means of getting to know each other with the aim of building a married life on solid foundations.     and strong foundations.      It also highlights how the sermon is held through modern electronic means because it is one of the houses of our time that our ancestors did not know before.         This research also shows the legal nature given by the Algerian legislator to the sermon, which he considered a promise of marriage and not a marriage contract that would allow both the suitor and the engaged to be pardoned at any time at any time, but in the case of recusal, this deviation has implications: compensation and the recovery or value of gifts.